A Comprehensive Analysis of Indonesia's Coffee Exports to the Global Market from 1991 to 2021 - Permana, Vebri Dwi; Patiung, Markus; Wisnujati, Nugrahini Susantinah (PT. Sangadji Media Publishing, 2024)
This study aims to analyze the factors influencing the decline in Indonesia's coffee exports and to formulate strategies to enhance these exports. Using a quantitative methodology, data from 1991 to 2021 were analyzed via regression analysis employing SPSS software. The independent variables considered included coffee production volume, harvested coffee land area, the GDP of the United States, and the exchange rate of the Indonesian Rupiah to the US Dollar. The results indicate that Indonesia's coffee production and harvested area significantly influence export volumes. The regression model developed demonstrated a moderate explanatory power with an R² value of 53%, indicating that the model explains 53% of the variance in coffee exports. The Analysis of Variance (ANOVA) test confirmed the model's significance, highlighting that the included variables collectively impact coffee exports. Partial t-test analysis revealed that the harvested area, producer coffee prices, and exchange rates are significant factors. The study concludes that enhancing the quality and competitiveness of Indonesian coffee, improving infrastructure, and adopting supportive government policies are crucial strategies to boost coffee exports. These efforts must address the challenges posed by global market dynamics, competition, and environmental factors to ensure the sustainable growth of Indonesia's coffee sector.